Evaluation of toxicity and antioxidant activities of various crude extracts of leaves and stems of Zygophyllum simplex - Noha Maher Galal; Salem Said Al Touby; Yahya Bin Abdullah Alrashdi; Mohammad Amzad Hossain (Advances in Biomarker Sciences and Technology)
Zygophyllum simplex (Z. simplex) is a plant that has been used for a long time for the treatment of human diseases. Therefore, this present research study aims to prepare various plant extracts and screen their antioxidant and cytotoxic activities. To attain the present objectives, different crude extracts were prepared from the leaves and stems of Z. simplex by using a maceration method. The activities of antioxidant and cytotoxic were prepared from aerial crude extracts of Z. simplex which were determined by 2,2-diphenyl-1-1-picrylhydrazyl (DPPH) and brine shrimp lethality (BSL) methods, respectively. All the prepared leaves and stems extracts of the selected plant at six different concentrations showed significant antioxidant activity against the DPPH method. The ethyl acetate crude extract showed the highest antioxidant activity and the lowest activity was in butanol extract. However, all the leaves and stems crude extracts of Z. simplex were prepared at different concentrations also showed promising cytotoxic activity against the BSL method. However, based on the antioxidant activity results, the ethyl acetate extract was selected for the isolation of bioactive compounds by using the column chromatographic method. The ethyl acetate was purified by using column chromatography in which different ratios of mobile phase (dichlorometane: methanol) were used. A series of test tubes were collected with a volume of 3 mL and depending on the similar retention mobility (Rf) behavior a total of twelve fractions were prepared. Similarly, the antioxidant activity of the obtained twelve fractions from column chromatography was determined by the same DPPH method. All the fractions showed significant antioxidant activity. Among the fractions from the column, fraction 6 give the highest antioxidant activity and the lowest was fraction 1. In conclusion, all the leaves and stems showed encouraging activities against DPPH and the fraction with the highest antioxidant activity could be used as a natural antioxidant to prevent cell damage.